A donzela Laida e o enigma da feiura em a demanda do Santo Graal - Schimid, Vanessa Annecchini (2017)
This work analyses the feminine ugliness in the Medieval context (13th century) by means of a study of the character laida in A demanda do Santo Graal, when considering the ambiguity of her figure and having in mind the importance of her benevolent function – to prevent the tragic destiny of Galvam – versus the adjective “ugly”, which she is given in order to not particularize her. Therefore, tries to understand such antagonistic aspects that configure the character’s ambiguity and its relation to the masculine perception of women in that period. It tries to prove the hypothesis that laida, in spite of the polarization that characterizes the feminine studies about A demanda do Santo Graal, in which woman is idealized under the light of courteous love or generally condemned by Christianity with the exception of Holly Mary, the aim of this dissertation is to prove the hypothesis that laida inscribes herself in a between place marked by Celtic and Christian cultures, inside a universe of evident misogynist and pedagogic tone.